THE PROGRAM AND COMPUTING COMPLEX FOR RESEARCHES OF LONGITUDINAL LOADING OF TANK CARS - Blokhin, Ye. P.; Harkavi, N. Ya.; Zheleznov, K. I.; Ursulyak, L. V.; Romanyuk, Ya. M. (Science and Transport Progress, 2010)
The description of the developed computer system possibilities and its use to solve problems of motion safety and stability is given.